Sodium ion positive electrode material, preparation method thereof and sodium ion battery
By introducing specific crystal structures and preparation methods into the positive electrode materials of sodium ion battery, the problems of low capacity and poor cycle life of the positive electrode materials of sodium ion battery are solved, and the effects of high capacity and excellent cycle performance are achieved, which is suitable for the industrial application of sodium ion batteries.
Patent Information
- Application Number
- CN202311229478.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
AI Technical Summary
The existing sodium ion battery positive electrode materials have low capacity and poor cycle life, which limits the commercial application of sodium ion batteries.
A sodium ion positive electrode material is provided that ensures the material has high capacity and excellent cycling properties through a specific crystal structure and preparation method, including a secondary sintering process and controlling sintering conditions.
Through specific crystal structures and preparation methods, the capacity and circulation performance of sodium ion batteries are improved, and the residual alkali content on the surface of the positive electrode material is reduced, making it suitable for large-scale industrial applications.
Smart Images

Figure CN119674182A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and in particular to a sodium ion positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the rapid growth of global battery demand and the uneven spatial distribution of lithium resources, the lithium-ion battery industry chain has begun to face the problem of lithium resource constraints. The biggest difference between sodium-ion batteries and lithium-ion batteries lies in the positive electrode material. The positive electrode material uses sodium resources, which will provide huge cost advantages for sodium-ion batteries.
[0003] Sodium-ion batteries have a long history. They came out almost at the same time as lithium-ion batteries in the 1970s. They have the same principle as lithium-ion batteries, but the development of sodium-ion batteries has not been smooth. It is difficult to find suitable positive electrode materials with sufficient electrochemical capacity and circulation to make them have certain commercial value.
[0004] At present, the research hotspots of sodium ion battery cathode materials mainly include polyanion compounds, Prussian blue compounds, and layered metal oxides (O3 and P2 types). However, compared with lithium ion battery cathode materials, these materials have high residual sodium carbonate, poor capacity and cycle life, or high preparation costs, which restricts the large-scale industrial application of sodium ion batteries.
[0005] CN113161543A provides a high energy density sodium ion battery positive electrode material and a preparation method thereof, but the prepared material is a polyanion material, and its gram specific capacity is only increased to 121 mAh / g.
[0006] CN115036487A provides a layered oxide sodium ion battery positive electrode material with a superstructure, whose gram-specific capacity is close to 140 mAh / g, but it uses a high content of expensive nanotube materials and lithium, has a high preparation cost, and is not suitable for large-scale industrial application. Summary of the invention
[0007] The purpose of the present invention is to solve the problems of low capacity and poor cycle life of existing sodium ion batteries, and to provide a sodium ion positive electrode material and a preparation method thereof, a sodium ion battery and application thereof. The sodium ion positive electrode material has a specific crystal structure, so that the sodium ion battery prepared therefrom has a higher capacity and excellent cycle stability.
[0008] In order to achieve the above object, the first aspect of the present invention provides a sodium ion positive electrode material, wherein the a-axis lattice constant and the c-axis lattice constant of the positive electrode material obtained by XRD satisfy:
[0009] 5a+1.015≤c≤5a+1.235.
[0010] A second aspect of the present invention provides a method for preparing a sodium ion positive electrode material, wherein the method comprises the following steps:
[0011] S1. Mixing a nickel source, an iron source, a manganese source and a compound optionally containing a G element to obtain a positive electrode material precursor;
[0012] S2, mixing a positive electrode material precursor, a sodium source and a compound optionally containing the G element, and performing a first sintering in an oxygen-containing atmosphere to obtain a primary sintered material; wherein the constant temperature time t1 of the first sintering satisfies: 5h≤t1≤25h;
[0013] S3, sintering the primary sintered material for a second time in an oxygen-containing atmosphere, and obtaining the sodium ion positive electrode material after crushing, wherein the temperature T1 of the first sintering and the temperature T2 of the second sintering satisfy: T2≥T1;
[0014] Wherein, in step S2, the amounts of the positive electrode material precursor, the sodium source and the G-containing element are such that 0.8≤n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]≤1.1.
[0015] The third aspect of the present invention provides a sodium ion positive electrode material prepared by the above preparation method.
[0016] A fourth aspect of the present invention provides a sodium ion battery, wherein the sodium ion battery comprises the above-mentioned sodium ion positive electrode material.
[0017] Through the above technical solution, the sodium ion positive electrode material and preparation method thereof, and the sodium ion battery provided by the present invention achieve the following beneficial effects:
[0018] The sodium ion positive electrode material provided by the present invention has a specific crystal structure. Specifically, the a-axis lattice constant and the c-axis lattice constant of the sodium ion positive electrode material provided by the present invention have a specific relationship, thereby making it easy for Na in the positive electrode material to diffuse in the sodium layer of the layered structure, so that the battery made of the positive electrode material has a higher capacity and excellent cycle performance.
[0019] Furthermore, the 2θ of the (003) diffraction peak of the sodium ion positive electrode material provided by the present invention obtained by XRD is located in a specific position range, indicating that the phase of the positive electrode material is pure phase and there is a high Na + The content also has an appropriate interlayer spacing, which provides a good channel for the extraction / embedding of sodium ions, thereby further improving the capacity and cycle performance of the battery made of the positive electrode material.
[0020] The present invention provides a preparation process for a sodium ion positive electrode material, which adopts a secondary sintering process, and controls the constant temperature time of the first sintering, the temperature of the second sintering being greater than or equal to the temperature of the first sintering, and the sodium ratio, so that the sintering sodium reaction can be more complete, thereby ensuring that the prepared sodium ion positive electrode material has the specific crystal structure described in the present invention, thereby ensuring that the battery prepared by the positive electrode material has a high capacity and excellent cycle performance. At the same time, the specific sintering process of the present invention can significantly reduce the residual alkali content on the surface of the positive electrode material.
[0021] Furthermore, the preparation method of the sodium ion positive electrode material provided by the present invention is simple, relatively low in cost, and suitable for industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the XRD spectrum of the positive electrode material A1 of Example 1;
[0023] Figure 2 This is the XRD spectrum of the positive electrode material D1 of Comparative Example 1. DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] A first aspect of the present invention provides a sodium ion positive electrode material, wherein the a-axis lattice constant and the c-axis lattice constant of the positive electrode material measured by XRD satisfy:
[0026] 5a+1.015≤c≤5a+1.235.
[0027] In the present invention, the positive electrode material is an O3 type layered oxide material, and belongs to the hexagonal system (Hexagonal), and the space group is R-3m. Specifically, the transition metal ions and sodium ions in the positive electrode material are alternately layered to occupy the octahedral position therein. The lattice constant in the a-axis direction is determined by the distance between the transition metal-transition metal and the sodium-sodium spacing, and the oxygen-oxygen distance, and the lattice constant in the c-axis direction is given by the layered 3 layers of transition metal-oxygen-sodium-oxygen stacking. When the sodium ion content in the sodium ion layer is increased, the electrostatic attraction between the sodium ions and the oxygen ions will be increased, and the repulsive force of the transition metal layer will be reduced, so the lattice constant will change accordingly. The inventors of the present invention have found that in the O3 type sodium ion layered oxide with a crystal structure of a specified size, the difference between the lattice constant of the a-axis and the lattice constant of the c-axis makes it easy for Na to diffuse in the sodium layer of the layered structure. The inventors of the present invention have found that when the lattice constant a of the a-axis and the lattice constant c of the c-axis satisfy 5a+1.015≤c≤5a+1.235, the sodium ions in the primary particles in the positive electrode material are more easily diffused, thereby further improving the capacity and cycle performance of the sodium ion battery made from the positive electrode material.
[0028] Further, 5a+1.035≤c≤5a+1.215, and further, 5a+1.065≤c≤5a+1.185.
[0029] According to the present invention, the 2θ position of the (003) diffraction peak of the positive electrode material measured by XRD satisfies:
[0030] 16.40°≤2θ (003) ≤16.80°.
[0031] In the present invention, the inventors have found that, for sodium ion positive electrode materials, the position of the (003) diffraction peak is closely related to the residual alkali content on the surface of the positive electrode material and the electrical properties of the positive electrode material. Further, the inventors have found that when the 2θ position of the (003) diffraction peak of the sodium ion positive electrode material measured by XRD satisfies the above range, the XRD of the positive electrode material has no obvious impurity diffraction peak, and when the positive electrode material is used to prepare a sodium ion battery, the capacity and cycle performance of the sodium ion battery can be significantly improved.
[0032] Furthermore, 16.50°≤2θ (003) ≤16.70°.
[0033] According to the present invention, the positive electrode material has a composition shown in Formula I:
[0034] Na α Ni x Fe y Mn z G gO2 Formula I;
[0035] Among them, 0.8≤α≤1.1, 0.1≤x≤0.5, 0.1≤y≤0.5, 0.1≤z≤0.8, 0≤g≤0.5, x+y+z+g=1, and G is selected from at least one of Li, Ti, Mg, Zn, Cu, Sr, Al, Zr, Y, Co, W, Ca, Nb, Sn, Sb, Mo, V, B, and Si.
[0036] In the present invention, the sodium ion positive electrode material has a specific sodium ratio (α value), which can ensure that the bulk phase of the positive electrode material contains a high content of Na + , so that the sodium ion battery made from the positive electrode material has improved capacity and cycle performance.
[0037] Further, 0.9≤α≤1.05, preferably, 0.95≤α≤1.05, more preferably, 1<α≤1.05; further preferably, 1<α≤1.03.
[0038] Further, 0.15≤x≤0.45, preferably, 0.20≤x≤0.40.
[0039] Further, 0.15≤y≤0.45, preferably, 0.20≤y≤0.40.
[0040] Further, 0.15≤z≤0.7, preferably, 0.20≤z≤0.60.
[0041] Further, 0<g≤0.30, preferably, 0<g≤0.20.
[0042] In a preferred embodiment of the present invention, G is selected from at least one of Al, Zn, Mg, Cu, Sr, Ca, Y, Sn, and B.
[0043] In a specific embodiment of the present invention, the sodium ion positive electrode material is further coated with a coating layer, wherein the coating layer is a sodium oxide and / or oxide of at least one element selected from V, Ta, Cr, La, Al, Ce, Y, Mg, Sr, Ni, Ba, Ra, Fe, Zr, Sn, Sb, Ca, Mn, Zn, B, W, Nb, Cd, Pb, Si, Mo, F, P, Co, Li, Ti and Cu.
[0044] According to the present invention, based on the total weight of the positive electrode material, the residual alkali content on the surface is ≤1.5wt%.
[0045] In the present invention, the positive electrode material has a low surface residual alkali (Na2CO3) content, so that the positive electrode material has a higher initial discharge specific capacity and less gas production, thereby making the sodium ion battery made from the positive electrode material have improved capacity and cycle performance.
[0046] Furthermore, based on the total weight of the positive electrode material, the residual alkali content on the surface is ≤1wt%.
[0047] A second aspect of the present invention provides a method for preparing a sodium ion positive electrode material, wherein the method comprises the following steps:
[0048] S1. Mixing a nickel source, an iron source, a manganese source and a compound optionally containing a G element to obtain a positive electrode material precursor;
[0049] S2, mixing a positive electrode material precursor, a sodium source and a compound optionally containing the G element, and performing a first sintering in an oxygen-containing atmosphere to obtain a primary sintered material; wherein the constant temperature time t1 of the first sintering satisfies: 5h≤t1≤25h;
[0050] S3, sintering the primary sintered material for a second time in an oxygen-containing atmosphere, and obtaining the sodium ion positive electrode material after crushing, wherein the temperature T1 of the first sintering and the temperature T2 of the second sintering satisfy: T2≥T1;
[0051] Wherein, in step S2, the amounts of the positive electrode material precursor, the sodium source and the G-containing element are such that 0.8≤n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]≤1.1.
[0052] In a specific embodiment of the present invention, the nickel source is preferably a nickel salt, the iron source is preferably an iron salt, the manganese source is preferably a manganese salt, and the compound optionally containing the G element is preferably a salt optionally containing the G element. When the nickel source, the iron source, the manganese source and the compound containing the G element are salts, preferably, the mixing includes: dissolving the nickel salt, the iron salt, the manganese salt and the salt optionally containing the G element in the presence of a solvent to obtain a mixed solution, and then mixing with a precipitant and a complexing agent for coprecipitation reaction to obtain a positive electrode material precursor.
[0053] The present invention provides a preparation process for a sodium ion positive electrode material, which adopts a secondary sintering process, and controls the constant temperature time of the first sintering, the temperature of the second sintering being greater than or equal to the temperature of the first sintering, and the sodium ratio, so that the sintering sodium reaction can be more complete, thereby ensuring that the prepared sodium ion positive electrode material has the specific crystal structure described in the present invention, thereby ensuring that the battery prepared by the positive electrode material has a high capacity and excellent cycle performance. At the same time, the specific sintering process of the present invention can significantly reduce the residual alkali content on the surface of the positive electrode material.
[0054] Furthermore, the constant temperature time t1 of the first sintering satisfies: 7h≤t1≤20h.
[0055] Furthermore, the temperature T1 of the first sintering and the temperature T2 of the second sintering satisfy: T2-T1≥5°C, preferably, 5°C≤T2-T1≤250°C; more preferably, 5°C≤T2-T1≤150°C.
[0056] Further, in step S2, the amount of the positive electrode material precursor, the sodium source and the G element is such that 0.9≤n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]≤1.05, preferably, 0.95≤n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]≤1.05, more preferably, 1<n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]≤1.05, further preferably, 1<n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]≤1.03.
[0057] According to the present invention, the concentration of oxygen in the oxygen-containing atmosphere is ≥ 20 vol%.
[0058] In the present invention, when the concentration of oxygen in the oxygen-containing atmosphere during the first sintering and the second sintering process is controlled to meet the above range, the sodium reaction can be promoted, the residual alkali (Na2CO3) content on the surface of the material can be reduced, and the Na in the lattice can be increased. + content, thereby improving the material capacity and cycle stability.
[0059] According to the present invention, the conditions for the first sintering include: heating from room temperature to T1 at a first heating rate v1, and maintaining a constant temperature t1 at T1; wherein, 0.5°C / min≤v1≤5°C / min, 800°C≤T1≤1100°C.
[0060] In the present invention, the first sintering is performed under the above-mentioned specific sintering conditions, so that a positive electrode material mainly composed of O3-type layered oxides can be obtained, and production efficiency can be improved and cost can be reduced.
[0061] Furthermore, 0.5°C / min≤v1≤3°C / min, 850°C≤T1≤1000°C.
[0062] According to the present invention, the second sintering conditions include: heating from room temperature to T2 at a second heating rate v2, and maintaining a constant temperature t2 at T2; wherein, 1°C / min≤v2≤15°C / min, 800°C≤T2≤1100°C, and 3h≤t2≤20h.
[0063] In the present invention, the second sintering is performed under the above-mentioned specific sintering conditions, which can further eliminate the impurity phase in the material, make the sodium reaction more complete, and further increase the Na content in the lattice of the obtained positive electrode material. + , and reduce the surface residual alkali content, further improving the capacity and cycle stability of the battery assembled with the positive electrode material.
[0064] Furthermore, 2°C / min≤v2≤8°C / min, 850°C≤T2≤1050°C, 5h≤t2≤15h.
[0065] According to the present invention, the nickel source, the iron source, the manganese source and the compound containing the G element make n(Ni):n(Fe):n(Mn):n(G)=x:y:z:g, wherein 0.1≤x≤0.5, 0.1≤y≤0.5, 0.1≤z≤0.8, 0≤g≤0.5.
[0066] In a specific embodiment of the present invention, when the nickel source is preferably a nickel salt, the iron source is preferably an iron salt, the manganese source is preferably a manganese salt, and the compound optionally containing the element G is preferably a salt optionally containing the element G, the nickel salt, the iron salt, the manganese salt, the salt containing the element G and the compound containing the element G make n(Ni):n(Fe):n(Mn):n(G)=x:y:z:g, wherein 0.1≤x≤0.5, 0.1≤y≤0.5, 0.1≤z≤0.8, and 0≤g≤0.5.
[0067] In the present invention, there is no particular limitation on the timing of introducing the G element, and it can be introduced during the preparation of the positive electrode material precursor or during the first sintering process, as long as the total amount of G element added meets the requirements of the present invention.
[0068] According to the present invention, the G element is selected from at least one of Li, Ti, Mg, Zn, Cu, Sr, Al, Zr, Y, Co, W, Ca, Nb, Sn, Sb, Mo, V, B, and Si.
[0069] In the present invention, there is no particular limitation on the types of the nickel source, iron source, manganese source and compound containing the G element, as long as they can provide Ni, Fe, Mn and G elements. For example, the nickel source, iron source, manganese source and compound containing the G element are each independently selected from at least one of salts, oxides and hydroxides containing Ni, Fe, Mn and G.
[0070] In the present invention, there is no particular limitation on the types of nickel salts, iron salts, manganese salts and salts containing the G element, and they may be conventional soluble salts in the art. For example, the nickel salts, iron salts, manganese salts and salts containing the G element are each independently at least one of sulfates, nitrates and chlorides containing Ni, Fe, Mn and G.
[0071] In the present invention, there is no particular limitation on the type of solvent, as long as the nickel salt, iron salt, manganese salt and salt containing the G element can be fully dissolved and mixed uniformly, such as water.
[0072] In the present invention, there is no particular limitation on the type of complexing agent, and conventional complexing agents in the art can be used. For example, the complexing agent is selected from at least one of ammonia water, ammonium bicarbonate, ammonium carbonate, citric acid and disodium ethylenediaminetetraacetate. The concentration of the complexing agent can be 2-11 mol / L.
[0073] In the present invention, there is no particular limitation on the type of precipitant, and conventional precipitants in the art may be used. For example, the precipitant is selected from at least one of NaOH, KOH and LiOH. The concentration of the precipitant may be 3-10 mol / L.
[0074] In the present invention, there is no particular limitation on the type of sodium source, and conventional sodium sources in the art, such as sodium carbonate, can be used.
[0075] In the present invention, there is no particular limitation on the conditions of the coprecipitation reaction, and the coprecipitation reaction can be carried out according to conventional coprecipitation reaction conditions in the art. Preferably, the coprecipitation reaction is carried out in a nitrogen atmosphere.
[0076] The third aspect of the present invention provides a sodium ion positive electrode material prepared by the above preparation method.
[0077] A fourth aspect of the present invention provides a sodium ion battery, wherein the sodium ion battery comprises the above-mentioned sodium ion positive electrode material.
[0078] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, unless otherwise specified, the raw materials used are all commercially available products.
[0079] In the following examples and comparative examples, the relevant parameters were tested by the following methods:
[0080] (1) The residual Na2CO3 content in the positive electrode material was tested by potentiometric acid-base titration; the instrument used was Aomi 888, and the test conditions were: 5 g of sample was added to 95 mL of pure water, magnetically stirred for 5 min, filtered, and the filtrate was removed for testing;
[0081] (2) The crystal structure of the positive electrode material was tested by XRD; the instrument used was an X-ray diffractometer (Rigaku, SmartLab 9KW), and the test conditions were: the X-ray source was Cu Kα rays, the scanning range was 10°-80°, the scanning rate was 1° / min, and the scanning step was 0.02°;
[0082] (3) Electrochemical performance test: In the following examples and comparative examples, the electrochemical performance of the positive electrode material was tested using an R2025 button-type sodium ion battery.
[0083] The preparation process of sodium ion battery is as follows:
[0084] Preparation of pole pieces: The sodium ion battery positive electrode material, conductive agent SuperP and polyvinylidene fluoride (PVDF) are mixed with an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 90:5:5 to form a uniform slurry. The slurry is coated on aluminum foil and dried at 120°C for 12 hours. It is then stamped into a positive electrode piece with a diameter of 12 mm and a thickness of 120 μm using a pressure of 100 MPa.
[0085] Battery assembly: In an argon-filled glove box with a water content and oxygen content of less than 5ppm, the positive electrode, separator, negative electrode and electrolyte were assembled into a R2025 button-type sodium-ion battery and left to stand for 6 hours. The negative electrode used a metal sodium sheet with a diameter of 14mm and a thickness of 1mm; the separator used a 25μm thick rubber-coated separator; the electrolyte used a mixture of 1mol / L NaPF6, ethyl methyl carbonate (EMC) and propylene carbonate (PC) in a ratio of 4:6.
[0086] Electrochemical performance test:
[0087] In the following examples and comparative examples, the electrochemical performance of the R2025 button-type sodium ion battery was tested using the Shenzhen Xinwell Battery Testing System (CT3008). The first charge and discharge capacity test conditions were 0.1C@2-4.0V, 25°C, and the constant voltage cutoff current was 0.02C; the cycle performance test conditions were 1.0C@2-4.0V, 25°C. The button-type sodium ion battery was subjected to constant current charge and discharge tests at 0.1C and 1C, respectively, to evaluate the charge and discharge specific capacity, rate, and cycle performance of the sodium ion battery positive electrode material. The higher the capacity retention rate during the cycle, the higher the material stability and the better the battery system cycle performance.
[0088] Example 1
[0089] S1: dissolving nickel sulfate, iron sulfate and manganese sulfate in a molar ratio of nickel, iron and manganese elements of 1:1:1 to obtain a 2 mol / L mixed salt solution; dissolving sodium hydroxide into a precipitant solution with a concentration of 8 mol / L; dissolving ammonia water into a complexing agent solution with a concentration of 10.4 mol / L; introducing the mixed salt solution, the precipitant solution and the complexing agent solution into a reactor to mix and perform a first coprecipitation reaction, and then continuously performing a crystal growth reaction under the protection of a nitrogen atmosphere, filtering the obtained precursor slurry, washing, drying the filter cake at 120°C and sieving to obtain a precursor.
[0090] S2: The above precursor is mixed with sodium carbonate and Al2O3 in a proportion, wherein n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]=1.01, and the content of Al element is 0.5% based on the total weight of the positive electrode material. The mixture is first sintered in an atmosphere with an oxygen concentration of 21 vol%, and the temperature is increased to T1=900°C at a rate of v1=1.5°C / min, and then kept at 900°C for t1=15h, and then cooled with the furnace, and the sintered material is crushed to obtain the first sintered material;
[0091] S3: The first sintered material is heated to T2 = 920 ° C (T2-T1 = 20 ° C) at a rate of v2 = 3 ° C / min, and the mixture is sintered for a second time in an atmosphere with an oxygen concentration of 90 vol%, and the temperature is kept constant for t2 = 10 h, and then the temperature is lowered with the furnace, and the sintered material is crushed and sieved to obtain O3 type layered oxide positive electrode material A1, which is composed of Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0092] Example 2
[0093] According to the method of Example 1, except that in step S2, n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]=1.03, and the rest are the same, an O3-type layered oxide positive electrode material A2 is obtained, the composition is Na 1.03 (Ni 0.32644 Fe 0.32644 Mn 0.32644 Al 0.02068 )O2.
[0094] Example 3
[0095] According to the method of Example 1, except that in step S2, n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]=0.97, and the rest are the same, an O3-type layered oxide material A3 is obtained, the composition of which is Na0.97 (Ni 0.32653 Fe 0.32653 Mn 0.32653 Al 0.02041 )O2.
[0096] Example 4
[0097] According to the method of Example 1, except that in step S2, n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]=0.90, and the rest are the same, an O3-type layered oxide material A4 is obtained, the composition of which is Na 0.90 (Ni 0.32662 Fe 0.32662 Mn 0.32662 Al 0.02013 )O2.
[0098] Example 5
[0099] According to the method of Example 1, except that in step S2, the constant temperature time t1 = 10h, the rest is the same, and an O3-type layered oxide positive electrode material A5 is obtained, the composition is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0100] Example 6
[0101] According to the method of Example 1, except that in step S2, the constant temperature time t1 = 6.5h, the rest is the same, to obtain an O3 type layered oxide positive electrode material A6, the composition of which is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2
[0102] Example 7
[0103] According to the method of Example 1, except that Al2O3 in step S2 is replaced by ZnO, the content of Zn element is 6.5% based on the total weight of the positive electrode material, and the rest are the same, an O3-type layered oxide positive electrode material A7 is obtained, the composition is Na 1.01 (Ni 0.29600 Fe 0.29600 Mn 0.29600 Zn 0.11200 )O2.
[0104] Example 8
[0105] According to the method of Example 1, except that in step S1, the molar ratio of nickel, iron and manganese elements is 1:2:2, and the rest are the same, an O3-type layered oxide positive electrode material A8 is obtained, the composition is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0106] Example 9
[0107] According to the method of Example 1, except that in step S2, T2 = 900°C (T2-T1 = 0°C), the rest are the same, and an O3-type layered oxide positive electrode material A9 is obtained, the composition of which is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0108] Example 10
[0109] According to the method of Example 1, except that in step S2, T1 = 800°C (T2-T1 = 120°C), the rest are the same, and an O3-type layered oxide positive electrode material A10 is obtained, the composition of which is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0110] Embodiment 11
[0111] According to the method of Example 1, except that in step S3, T2 = 910 ° C (T2-T1 = 10 ° C), the rest are the same, and an O3-type layered oxide positive electrode material A11 is obtained, the composition is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2
[0112] Example 12
[0113] According to the method of Example 1, except that in step S3, T2 = 1050 ° C (T2-T1 = 150 ° C), the rest are the same, and an O3-type layered oxide positive electrode material A12 is obtained, the composition is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0114] Embodiment 13
[0115] According to the method of Example 1, except that in step S3, T2 = 903 ° C (T2-T1 = 3 ° C), the rest are the same, and an O3-type layered oxide positive electrode material A13 is obtained, the composition is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0116] Embodiment 14
[0117] According to the method of Example 1, except that in step S3, the oxygen content of the sintering atmosphere is 21 vol%, and the rest is the same, an O3-type layered oxide positive electrode material A14 is obtained, the composition is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0118] Embodiment 15
[0119] According to the method of Example 1, except that in step S2, T1=700°C (T2-T1=220°C), the rest are the same, and an O3-type layered oxide positive electrode material A15 is obtained, the composition of which is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0120] Example 16
[0121] According to the method of Example 1, except that in step S3, T2=1150°C (T2-T1=250°C), the rest are the same, and an O3-type layered oxide positive electrode material A16 is obtained, the composition is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0122] Embodiment 17
[0123] According to the method of Example 1, except that Al2O3 is not added in step S2, the rest is the same, and an O3-type layered oxide positive electrode material A17 is obtained, which has a composition of Na 1.01 (Ni 0.33333 Fe 0.33333 Mn 0.33333 )O2Comparative Example 1
[0124] According to the method of Example 1, except that the constant temperature time t1 in step S2 is 4h, the rest is the same, and an O3-type layered oxide positive electrode material D1 is obtained, the composition is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0125] Comparative Example 2
[0126] According to the method of Example 1, except that in step S2, n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]=0.78, and the rest are the same, an O3-type layered oxide material D2 is obtained, the composition of which is Na 0.78 (Ni 0.32679 Fe 0.32679 Mn 0.32679 Al 0.01962 )O2.
[0127] Comparative Example 3
[0128] According to the method of Example 1, except that in step S3, T2 = 850°C (T2-T1 = -50°C), the rest are the same, and an O3-type layered oxide positive electrode material D3 is obtained, the composition is Na 1.01 (Ni 0.3265 Fe 0.3265 Mn 0.3265 Al 0.0205 )O2.
[0129] Comparative Example 4
[0130] According to the method of Example 1, except that in step S2, T2 = 895 ° C (T2-T1 = -5 ° C), the rest are the same, and an O3-type layered oxide positive electrode material D4 is obtained, the composition is Na 1.01 (Ni 0.32647 Fe 0.32647 Mn 0.32647 Al 0.02059 )O2.
[0131] Test Case
[0132] (1) Residual Na2CO3 test and XRD test:
[0133] The present invention tests the residual Na2CO3 content and XRD of the positive electrode materials in the above-mentioned embodiments and comparative examples, and exemplarily provides the XRD spectra of the positive electrode material A1 prepared in Example 1 and the positive electrode material D1 prepared in Comparative Example 1. The results are as follows: Figure 1 and Figure 2 As shown. Figure 1 and Figure 2It can be seen that the O3 type positive electrode material prepared by the method of the present invention has no obvious impurity diffraction characteristic peak and the physical phase is pure.
[0134] The residual Na2CO3 content of the positive electrode materials prepared in the above embodiments and comparative examples, the characteristic diffraction peak position 2θ(003) of the XRD (003) peak, and the a-axis and c-axis unit cell parameters calculated based on the XRD spectrum are specifically shown in Table 1.
[0135] (2) Half-cell test
[0136] The present invention tests the electrochemical properties of the sodium ion battery positive electrode materials prepared in the above embodiments and comparative examples, including 0.1C first discharge specific capacity, 1C discharge specific capacity, and cycle performance. The specific test results are shown in Table 2.
[0137] Table 1
[0138]
[0139]
[0140] Table 2
[0141]
[0142]
[0143] It can be seen from Tables 1 and 2 that the sodium ion positive electrode material prepared by the preparation method provided by the present invention is an O3 type layered oxide material with a specific crystal structure and a low surface residual alkali (Na2CO3). The sodium ion battery made using the material provided by the present invention has a higher capacity, rate and cycle life.
[0144] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A sodium ion positive electrode material, characterized in that: The a-axis lattice constant and c-axis lattice constant of the positive electrode material measured by XRD satisfy: 5a+1.015≤c≤5a+1.235, preferably, 5a+1.035≤c≤5a+1.215, more preferably, 5a+1.065≤c≤5a+1.
185.
2. The sodium ion positive electrode material according to claim 1, wherein The 2θ position of the (003) diffraction peak of the positive electrode material measured by XRD satisfies: 16.40°≤2θ (003) ≤16.80°, preferably, 16.50°≤2θ (003) ≤16.70°.
3. The sodium ion positive electrode material according to claim 1 or 2, wherein The positive electrode material is an O3-type layered oxide; Preferably, the positive electrode material has a composition shown in Formula I: Na α Ni x Fe y Mn z G g O2 formula I; Wherein, 0.8≤α≤1.1, 0.1≤x≤0.5, 0.1≤y≤0.5, 0.1≤z≤0.8, 0≤g≤0.5, x+y+z+g=1, and G is selected from at least one of Li, Ti, Mg, Zn, Cu, Sr, Al, Zr, Y, Co, W, Ca, Nb, Sn, Sb, Mo, V, B, and Si; Preferably, 0.9≤α≤1.05, 0.15≤x≤0.45, 0.15≤y≤0.45, 0.15≤z≤0.7, 0<g≤0.30; Preferably, 1<α≤1.
05.
4. The sodium ion positive electrode material according to any one of claims 1 to 3, wherein Based on the total weight of the positive electrode material, the residual alkali content on the surface is ≤1.5wt%, preferably ≤1wt%.
5. A method for preparing a sodium ion positive electrode material, characterized in that: The method comprises the following steps: S1. Mixing a nickel source, an iron source, a manganese source and a compound optionally containing a G element to obtain a positive electrode material precursor; S2, mixing a positive electrode material precursor, a sodium source and a compound optionally containing the G element, and performing a first sintering in an oxygen-containing atmosphere to obtain a primary sintered material; wherein the constant temperature time t1 of the first sintering satisfies: 5h≤t1≤25h; S3, sintering the primary sintered material for a second time in an oxygen-containing atmosphere, and obtaining the sodium ion positive electrode material after crushing, wherein the temperature T1 of the first sintering and the temperature T2 of the second sintering satisfy: T2≥T1; Wherein, in step S2, the positive electrode material precursor, the sodium source and the compound containing the G element are used in an amount such that 0.8≤n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]≤1.1; Preferably, the mixing in step S1 comprises: dissolving nickel salt, iron salt, manganese salt and optionally a salt containing element G in the presence of a solvent to obtain a mixed solution, and then mixing the mixed solution with a precipitant and a complexing agent to perform a co-precipitation reaction to obtain a positive electrode material precursor.
6. The method according to claim 5, wherein: The constant temperature time t1 of the first sintering satisfies: 7h≤t1≤20h; Preferably, the temperature T1 of the first sintering and the temperature T2 of the second sintering satisfy: T2-T1≥5°C; Preferably, in step S2, the amounts of the positive electrode material precursor, the sodium source and the G-containing element are such that 0.9≤n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(G)]≤1.
05.
7. The method according to claim 5 or 6, wherein: The concentration of oxygen in the oxygen-containing atmosphere is ≥20 vol%; Preferably, the first sintering conditions include: heating from room temperature to T1 at a first heating rate v1, and maintaining a constant temperature t1 at T1; wherein 0.5°C / min≤v1≤5°C / min, 800°C≤T1≤1100°C; Preferably, the second sintering conditions include: heating from room temperature to T2 at a second heating rate v2, and maintaining a constant temperature t2 at T2; wherein, 1°C / min≤v2≤15°C / min, 800°C≤T2≤1100°C, and 3h≤t2≤20h.
8. The method according to any one of claims 5 to 7, wherein: The nickel source, the iron source, the manganese source and the compound containing the G element are such that n(Ni):n(Fe):n(Mn):n(G)=x:y:z:g, wherein 0.1≤x≤0.5, 0.1≤y≤0.5, 0.1≤z≤0.8, 0≤g≤0.5; Preferably, the nickel salt, the iron salt, the manganese salt, the salt containing the G element and the compound containing the G element are such that n(Ni):n(Fe):n(Mn):n(G)=x:y:z:g, wherein 0.1≤x≤0.5, 0.1≤y≤0.5, 0.1≤z≤0.8, 0≤g≤0.5; Preferably, the G element is selected from at least one of Li, Ti, Mg, Zn, Cu, Sr, Al, Zr, Y, Co, W, Ca, Nb, Sn, Sb, Mo, V, B, and Si.
9. A sodium ion positive electrode material prepared by the method according to any one of claims 5 to 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion positive electrode material according to any one of claims 1 to 4 and 9.
Citation Information
Patent Citations
High-energy-density sodium ion battery positive electrode material as well as preparation method and application thereof
CN113161543A